Vulnerability Assessment pada Situs XYZ Menggunakan Web Vulnerability Scanner Burp Suite - Syani, Mamay; Taufik Fajar Mustafa; Maalik Falah, Hafizh; Rohayati, Tuti; Abdul Rosid, Usep (Jurnal Sistem Informasi Galuh, 2025)
The increasing adoption of digital services by local governments demands greater attention to cybersecurity aspects. This study applies the penetration testing method using a Blue Teaming approach on XYZ, a web-based public service portal using Burp Suite tools, to identify potential security vulnerabilities. The testing follows the NIST SP 800-115 guidelines and reveals 16 vulnerabilities classified as low to medium severity. Findings indicate weaknesses such as cookies without Secure and HttpOnly attributes, the use of vulnerable JavaScript libraries, and the absence of HSTS policy. Recommendations are provided to help site administrators enhance overall system security resilience.